Factors affecting place of delivery in Dhading district - Adhikari, RK; Dahal, LH (Journal of Institute of Medicine Nepal, 2009)
Background: Nepal is one of countries having highest maternal mortality ratio of 539 per 100,000 live births, with 9.9% health institutional deliveries and where 67% maternal deaths occur at home. The present study aimed to determine the factors affecting place of delivery in Dhading district for the quantification of the factors to help in planning and implementation of safe motherhood programme in Dhading district. Material and Methods: The study was conducted in community and health institutions based cross- sectional comparative design. For this purpose all the 400 mothers of 4 village development committees of Salyantar, Dhuwakot, Tripureshwor and Darkha of Dhading district who delivered babies in the period of January 15, 2007 to January 14, 2008 were selected in the study by using female community health volunteers, Focus Group Discussion. The village development committees were selected by cluster sampling design. Result: The study indicated that the odds of home deliveries among the illiterate mothers was 3.22 times higher compared to literate mothers (1.43-7.48 at 95% confidence limit; p= 0.002). Similarly the study has shown that the odds of home deliveries among multiparous mothers was 2.54 times higher than the primiparous mothers (1.27-5.13 at 95% confidence limit; p=0.002). Similarly the study has shown that the odds of home delivery in Tamang was 3.74 times higher than in ethnic group other than Tamang (1.37-5.19 at 95% confidence limit; p=0.004). These findings suggest that the maternal education, ethnicity, and parity have statistically significant effects to home and health institutional deliveries. Conclusion: From these findings it is recommended that the Safer Motherhood Programme of Dhading district should give priority to the Tamang Commutity and focus needs to be given to the education to the girls and Family Planning Programme needs to be strengthened. Key words: Safe motherhood, delivery, home, health institution, factors, Dhading. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 42-48